IMPLEMENTASI PERATURAN MENTERI AGRARIA DAN TATA RUANG/ KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 16 TAHUN 2019 TENTANG PENYELENGGARAAN SISTEM PENGENDALIAN INTERN PEMERINTAH DI LINGKUNGAN KEMENTERIAN AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL KOTA PEKANBARU - Mahani Mahani; Dessy Artina; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research relates to the Implementation of Internal Control Based on theRegulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the NationalDefense Agency of the Republic of Indonesia Number 16 of 2019 concerning theImplementation of the Government's Internal Control System within the Ministry of AgrarianAffairs and Spatial Planning/National Defense Agency of Pekanbaru City. In the field,internal supervision has not yet been carried out at the Pekanbaru City Land Agency, whichcan be seen from the absence of a clear flow of supervision and the absence of a report on theresults of internal supervision to the Pekanbaru City Inspectorate as well as reports submittedto Commission 1 DPRD Pekanbaru City as one of the external supervisors from thePekanbaru City National Land Agency. Therefore it is necessary to study the first stimulant,internal supervision is appropriate. with the Regulation of the Minister of Agrarian Affairsand Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number16 of 2019 at the Pekanbaru City National Land Agency. Second, the supporting andinhibiting factors in implementing the Regulation of the Minister of Agrarian Affairs andSpatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 16of 2019 at the Pekanbaru City National Land Agency.This research is a sociological law research, because it is based on field research,namely by collecting data from observation, interviews, and literature studies that have arelationship with the problems studied assisted by primary, secondary, and tertiary data. Thisstudy uses qualitative data analysis, produces descriptive data, and concludes with adeductive thinking method.From the research results there are three main things that can be concluded. First,internal supervision at the Pekanbaru City Land Agency has not yet been carried out inaccordance with the Regulation of the Minister of Agrarian Affairs and SpatialPlanning/Head of the National Land Agency of the Republic of Indonesia Number 16 of 2019concerning Implementation of the Government Internal Control System within the NationalLand Agency, this can be seen from the absence a clear flow of supervision and there is noreport on the results of internal supervision to the Pekanbaru City Inspectorate or a reportsubmitted to Commission 1 of the Pekanbaru City DPRD as one of the external supervisorsfrom the Pekanbaru City National Land Agency.Keywords:Implementation-Internal Oversight-National Land Agency